2000
DOI: 10.1063/1.1309055
|View full text |Cite
|
Sign up to set email alerts
|

Doping of n-type 6H–SiC and 4H–SiC with defects created with a proton beam

Abstract: Deep centers in n-type 4H–SiC and 6H–SiC irradiated with 8 MeV protons have been investigated by capacitance spectroscopy and electron paramagnetic resonance (EPR). Samples were fabricated by sublimation epitaxy or commercially produced by CREE Inc. Research Triangle Park, NC. It is showed that irradiation of wide-band gap semiconductors may lead to an increase in the concentration of uncompensated donors in an n-type material. The spectrum of deep centers in both SiC polytypes is independent of the technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
48
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(58 citation statements)
references
References 12 publications
10
48
0
Order By: Relevance
“…An annealing study of neutron irradiated 4H-SiC using ESR and optical absorption showed that the optical transition at 780 nm (1.59 eV), which is comparable to the RD 4 energy level, is originating from V Si [83]. The RD 5 levels at around E C -0.5 eV in 6H-SiC (same as L 6 , E i ) [54,57,58,63,66] are reported to show the similar annealing behavior to V C below 500…”
Section: Correlation Between Positron Annihilation Centers and Electrmentioning
confidence: 62%
See 3 more Smart Citations
“…An annealing study of neutron irradiated 4H-SiC using ESR and optical absorption showed that the optical transition at 780 nm (1.59 eV), which is comparable to the RD 4 energy level, is originating from V Si [83]. The RD 5 levels at around E C -0.5 eV in 6H-SiC (same as L 6 , E i ) [54,57,58,63,66] are reported to show the similar annealing behavior to V C below 500…”
Section: Correlation Between Positron Annihilation Centers and Electrmentioning
confidence: 62%
“…As for the other energy levels, the R levels appearing at E C -1.1∼1.3 eV in 6H-SiC (same as E 7 and L 10 ) [54,57,63] are attributed to V Si in the PAS study [44]. The R level shown in Fig.…”
Section: Correlation Between Positron Annihilation Centers and Electrmentioning
confidence: 91%
See 2 more Smart Citations
“…By comparing the removal rates of holes in various SiC polytypes (see table 1), we find that the acceptor compensation is more efficient for the 6H polytype than for the 4H polytype. We have shown previously that these ratios are inverted for the n-type material and the removal rate of electrons for the 4H polytype is several times that for the 6H polytype [15].…”
Section: [15] *) Results Of the Present Studymentioning
confidence: 95%